Targeting Piezo1 channel to alleviate intervertebral disc degeneration - Feiyun Li; Mingjue Chen; Mengrui Zhang; Sheng Chen; Minghao Qu; Shuangshuang He; Lin Wang; Xiaohao Wu; Guozhi Xiao (Journal of Orthopaedic Translation)
Background: Low back pain impacts over 600 million people worldwide, predominantly due to intervertebral disc degeneration. This study focuses on the role of Piezo1, a crucial mechanosensitive ion channel protein, in the pathology and potential treatment of disc degeneration. Materials and methods: To investigate the effects of disc-specific Piezo1 deletion, we generated AggrecanCreERT2; Piezo1fl/fl mice and examined both lumbar spine instability (LSI)- and aging-induced disc degeneration. Additionally, the effect of pharmacological inhibition of Piezo1 was evaluated using GsMTx4, a potent Piezo1 antagonist, in an ex vivo model stimulated with IL-1β to induce disc degeneration. Assessments included histological examinations, immunofluorescence, and western blot analyses to thoroughly characterize the alterations in the intervertebral discs. Results: Elevated expression of Piezo1 was detected in the nucleus pulposus (NP) of intervertebral discs with advanced disc degeneration in both aged mice and human patients. Inducible deletion of Piezo1 expression in aggrecan-expressing disc cells significantly reduced lumbar disc degeneration, decreased extracellular matrix (ECM) degradation, and lowered apoptosis in NP cells, observed in both aged mice and those undergoing LSI surgery. Excessive compression loading (CL) upregulated Piezo1 expression, induced ECM disruption, and increased apoptosis in NP cells, whereas inhibition of Piezo1 with GsMTx4 effectively mitigated these pathological changes. Furthermore, in ex vivo cultured mouse discs, GsMTx4 treatment significantly alleviated IL-1β-induced degenerative damages, restored ECM anabolism, and reduced apoptosis. Conclusions: The findings suggest that Piezo1 plays a critical role in the development of disc degeneration and highlight its potential as a therapeutic target. Inhibiting Piezo1 could offer a novel strategy for treating or preventing this critical disease. Translational potential of this article: This research highlights the involvement of Piezo1 in the development of intervertebral disc degeneration and emphasizes the potential for targeting Piezo1 as a therapeutic strategy to delay or reverse this condition.